2017
DOI: 10.1515/aopf-2017-0012
|View full text |Cite
|
Sign up to set email alerts
|

Great cormorant (Phalacrocorax carbo) predation on pikeperch (Sander lucioperca L.) in shallow eutrophic lakes in Poland

Abstract: Abstract. Increases in the population abundance of the piscivorous great cormorant (Phalacrocorax carbo) has led to conflicts with fisheries. Cormorants are blamed for decreased fish catches in many lakes in Poland. The aim of this paper is to describe to role of pikeperch (Sander lucioperca) in the diet of cormorants nesting in a colony on the island in Lake Warno³ty. Since the breeding colony is located in the vicinity of Lake OEniardwy, the largest lake in Poland, the cormorants use the resources in this la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
(9 reference statements)
1
1
0
Order By: Relevance
“…Lake Warnołty is an example of water bodies being under limited human activities and legal protection (nature reserve) of the breeding and hunting sites for a lot of wetland birds including cormorants, which are the top piscivorous predators. Recently, the pressure of cormorants (inhabiting the Warnowska island) on this lake and neighboring Lake Śniardwy has become much stronger compared to 2005 [25]. Our studies confirmed that the highest content of nutrients (primarily phosphorus) and chlorophyll a simultaneously with the lowest water transparency were observed in the area closely related to that island.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Lake Warnołty is an example of water bodies being under limited human activities and legal protection (nature reserve) of the breeding and hunting sites for a lot of wetland birds including cormorants, which are the top piscivorous predators. Recently, the pressure of cormorants (inhabiting the Warnowska island) on this lake and neighboring Lake Śniardwy has become much stronger compared to 2005 [25]. Our studies confirmed that the highest content of nutrients (primarily phosphorus) and chlorophyll a simultaneously with the lowest water transparency were observed in the area closely related to that island.…”
Section: Discussionsupporting
confidence: 80%
“…They can increase the concentrations of nitrogen, phosphorus, dissolved organic carbon, and electrical conductivity, while reducing water transparency. Cormorants cause local or global changes in species structure towards more eutrophic species of algae and macrophytes, which lead to microbial pollution [72], and in abundance, species composition, and size-age structure of fish communities [25], which in turn may have a significant impact on the lower trophic levels.…”
Section: Discussionmentioning
confidence: 99%